The Role of Imaging Biomarkers to Guide Pharmacological Interventions Targeting Tumor Hypoxia - Gallez, Bernard (Frontiers in Pharmacology, 2022)
Hypoxia is a common feature of solid tumors that contributes to angiogenesis, invasiveness, metastasis, altered metabolism and genomic instability. As hypoxia is a major actor in tumor progression and resistance to radiotherapy, chemotherapy and immunotherapy, multiple approaches have emerged to target tumor hypoxia. It includes among others pharmacological interventions designed to alleviate tumor hypoxia at the time of radiation therapy, prodrugs that are selectively activated in hypoxic cells or inhibitors of molecular targets involved in hypoxic cell survival (i.e. hypoxia inducible factors HIFs, PI3K/AKT/mTOR pathway, unfolded protein response). While numerous strategies were successful in pre-clinical models, their translation in the clinical practice has been disappointing so far. This therapeutic failure often results from the absence of appropriate stratification of patients that could benefit from targeted interventions as well from the lack of adaptative protocols based on the dynamic evolution of tumor hypoxia. To give a real chance to promising strategies, there is a crucial need for inclusion of companion diagnostics focused on hypoxia that may help at different levels of the research and development. Based on the relative merits of the hypoxic biomarkers and on the nature of the pharmacological target, we define strategies for coupling biomarkers and interventions, and we illustrate pre-clinical/clinical approaches for a successful translation in patients.